Resin film, coverlay film, circuit board, resin-coated copper foil, metal-clad laminate, multi-layer circuit board, polyimide and adhesive resin composition

JP7630226B2Active Publication Date: 2025-02-17NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019164507
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-09-10
Publication Date
2025-02-17
Estimated Expiration
2039-09-10

Smart Images

  • Figure 0007630226000001
    Figure 0007630226000001
  • Figure 0007630226000002
    Figure 0007630226000002
  • Figure 0007630226000003
    Figure 0007630226000003
Patent Text Reader

Abstract

To provide a resin film that has dielectric characteristics suppressed in humidity dependency while meeting the demand for a higher frequency in an electronic apparatus by improving dielectric characteristics and to provide a polyimide.SOLUTION: The resin film contains as a resin component a polyimide produced by reacting a tetracarboxylic acid anhydride component with a diamine component in which the diamine component contains a dimer diamine composition composed mainly of dimer diamine in an amount of 40 mol% or more based on the total diamine components, and has an Evalue of 0.010 or less, which is calculated based on (i): E=√ε×Tanδand is an index showing dielectric characteristics at 10 GHz after 24-hour humidity conditioning under the conditions of constant temperature and constant humidity of 23°C and 50% RH and a ratio (E / E) of an Evalue to the Evalue in the range of 3.0 to 1.0 in the Evalue which is calculated based on (ii): E=√ε×Tanδand is an index showing dielectric characteristics at 10 GHz after 24-hour water absorption at 23°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide useful as an adhesive in circuit boards such as printed wiring boards, and to uses thereof. [Background technology]

[0002] In recent years, with the progress of miniaturization, weight saving, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for moving parts of electronic devices such as HDDs, DVDs, and mobile phones, as well as components such as cables and connectors.

[0003] In addition to the above-mentioned increase in density, the advancement of equipment performance has created a need to accommodate higher frequencies of transmission signals. In the fields of information processing and communications, efforts are being made to increase transmission frequencies in order to transmit and process large volumes of information, and printed circuit board materials are being required to reduce transmission loss by thinning the insulating layer and improving the dielectric properties of the insulating layer. In the future, FPCs and adhesives that can handle higher frequencies will be required, and reducing transmission loss will be important.

[0004] Incidentally, as a technique for an adhesive layer mainly composed of polyimide, it has been proposed to apply a crosslinked polyimide resin obtained by reacting a polyimide made from a diamine compound derived from an aliphatic diamine such as dimer acid (dimer fatty acid) with an amino compound having at least two primary amino groups as functional groups to the adhesive layer of a coverlay film (for example, Patent Document 1). It has also been proposed to apply a resin composition using such a polyimide, a thermosetting resin such as an epoxy resin, and a crosslinking agent in combination to a copper-clad laminate (for example, Patent Document 2). However, Patent Documents 1 and 2 do not take into consideration the influence of by-products other than the dimer diamine derived from the dimer acid contained in the raw material.

[0005] Dimer acids are dimerized fatty acids obtained by subjecting natural fatty acids, such as soybean oil fatty acids, tall oil fatty acids, rapeseed oil fatty acids, and the like, as well as oleic acid, linoleic acid, linolenic acid, erucic acid, and the like, which are obtained by refining these fatty acids, as raw materials, and it is known that polybasic acid compounds derived from dimer acids are obtained as compositions of the raw material fatty acids and trimerized or higher fatty acids (e.g., Patent Document 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-1730 A [Patent Document 2] JP 2017-119361 A [Patent Document 3] JP 2017-137375 A Summary of the Invention [Problem to be solved by the invention]

[0007] As a means of controlling the physical properties of a resin mainly composed of polyimide, it is important to control the molecular weight of polyamic acid or polyimide, which is a precursor of polyimide. However, when dimer diamine is used as a raw material, it is used in a state containing by-products other than dimer diamine derived from dimer acid. Such by-products make it difficult to control the molecular weight of polyimide, and also affect its dielectric properties over a wide frequency range and its humidity dependency.

[0008] An object of the present invention is to provide a resin film and polyimide having dielectric properties that are improved to enable electronic devices to operate at higher frequencies and that have reduced humidity dependency. [Means for solving the problem]

[0009] The resin film of the present invention is a resin film containing a polyimide as a resin component, and the polyimide is obtained by reacting a tetracarboxylic acid anhydride component with a diamine component. The diamine component contains 40 mol % or more of a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine component. The resin film of the present invention satisfies the following configurations I and II.

[0010] I) The following formula (i): E1 = √ε1 × Tan δ1 (i) [Here, ε1 indicates the dielectric constant at 10 GHz measured by a split post dielectric resonator (SPDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, and Tanδ1 indicates the dielectric tangent at 10 GHz measured by an SPDR after 24 hours of humidity conditioning under constant temperature and humidity conditions of 23°C and 50% RH] The E1 value, which is an index of dielectric properties at 10 GHz after 24 hours of conditioning at constant temperature and humidity conditions of 23°C and 50% RH, calculated based on the above, is 0.010 or less.

[0011] II) The following formula (ii): E2 = √ε2 × Tan δ2 (ii) [Here, ε2 indicates the dielectric constant at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours, and Tanδ2 indicates the dielectric tangent at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours] The E2 value, which is an index of dielectric properties at 10 GHz after absorbing water for 24 hours at 23°C, is calculated based on the following: The ratio of the E2 value to the E1 value (E2 / E1) is within the range of 3.0 to 1.0.

[0012] In addition, in formulas (i) and (ii), “√ε1” and “√ε2” mean the square roots of “ε1” and “ε2”, respectively.

[0013] The coverlay film of the present invention is a coverlay film in which an adhesive layer and a coverlay film material layer are laminated together, and the adhesive layer is made of the above-mentioned resin film.

[0014] The circuit board of the present invention includes a substrate, a wiring layer formed on the substrate, and the above-mentioned coverlay film that covers the wiring layer.

[0015] The resin-coated copper foil of the present invention is a resin-coated copper foil in which an adhesive layer and a copper foil are laminated together, and the adhesive layer is made of the above-mentioned resin film.

[0016] The metal-clad laminate of the present invention is a metal-clad laminate having an insulating resin layer, an adhesive layer laminated on at least one side of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, wherein the adhesive layer is made of the above-mentioned resin film.

[0017] The multilayer circuit board of the present invention is a multilayer circuit board comprising a laminate including a plurality of laminated insulating resin layers and one or more conductor circuit layers embedded inside the laminate. In the multilayer circuit board of the present invention, at least one of the plurality of insulating resin layers is formed of an adhesive layer having adhesiveness and covering the conductor circuit layer, and the adhesive layer is made of the above-mentioned resin film.

[0018] The polyimide of the present invention is obtained by reacting a tetracarboxylic anhydride component with a diamine component, and the diamine component contains 40 mol % or more of a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine component. The polyimide of the present invention has the following components (a) to (c), as determined by area percentage of a chromatogram obtained by measuring the dimer diamine composition using gel permeation chromatography: (a) dimer diamine; (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The content of the component (c) in the composition is 2% or less.

[0019] The polyimide of the present invention may contain 50 mol % or more of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) based on the total amount of the tetracarboxylic anhydride component.

[0020] The adhesive resin composition of the present invention comprises the following components (A) and (B): (A) the polyimide, and (B) an amino compound having at least two primary amino groups as functional groups; Including, The component (B) is contained so that the primary amino groups are contained in a total amount within a range of 0.004 mol to 1.5 mol per 1 mol of the ketone group of the BTDA residue derived from BTDA in the component (A). Effect of the Invention

[0021] The resin film and polyimide of the present invention have low humidity dependency of dielectric properties and excellent stability because the content of amine compounds other than dimer diamine in the dimer diamine composition is controlled. Therefore, the resin film and polyimide of the present invention can be particularly suitably used for circuit boards such as FPCs in electronic devices requiring high-speed signal transmission. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, an embodiment of the present invention will be described.

[0023] <Resin film> The resin film of the present embodiment is formed by forming a film with a resin component as a main component. In order to impart excellent high frequency characteristics and stability against humidity, the resin film of the present embodiment contains, as a resin component, a polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component containing 40 mol % or more of a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group, based on the total diamine components. The resin film of the present embodiment may contain, for example, a filler as an optional component other than the resin component.

[0024] (Dielectric properties) The resin film of the present embodiment is represented by the following formula (i): E1 = √ε1 × Tan δ1 (i) [Here, ε1 indicates the dielectric constant at 10 GHz measured by a split post dielectric resonator (SPDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23°C and 50% RH, and Tanδ1 indicates the dielectric tangent at 10 GHz measured by an SPDR after 24 hours of humidity conditioning under constant temperature and humidity conditions of 23°C and 50% RH] The E1 value, which is an index of dielectric properties at 10 GHz after 24 hours of humidity conditioning under constant temperature and humidity conditions of 23°C and 50% RH, calculated based on the above formula, is 0.010 or less, preferably 0.009 or less, and more preferably 0.008 or less. If the E1 value exceeds the upper limit, problems such as loss of electrical signals are likely to occur in the transmission path of high-frequency signals when the material is used in a circuit board such as an FPC.

[0025] (Dielectric constant) In order to ensure impedance matching when used in a circuit board such as an FPC and to reduce loss of an electric signal, the resin film of the present embodiment has a dielectric constant (ε1) at 10 GHz after 24 hours of conditioning under constant temperature and humidity conditions of 23° C. and 50% RH of preferably 3.2 or less, more preferably 3.0 or less. If the dielectric constant exceeds 3.2, problems such as loss of an electric signal are likely to occur on the transmission path of a high-frequency signal when used in a circuit board such as an FPC.

[0026] (Dielectric tangent) In addition, in order to reduce the loss of an electric signal when the resin film of the present embodiment is used in a circuit board such as an FPC, the dielectric loss tangent (Tan δ1) at 10 GHz after 24 hours of humidity control under constant temperature and humidity conditions of 23° C. and 50% RH is preferably less than 0.005, more preferably 0.004 or less. If the dielectric loss tangent is 0.005 or more, when the resin film is used in a circuit board such as an FPC, problems such as loss of an electric signal are likely to occur on the transmission path of a high-frequency signal.

[0027] (moisture absorption dependence) In order to reduce loss of electrical signals and ensure impedance matching in both dry and wet conditions when used in a circuit board such as an FPC, the resin film of the present embodiment has a structure represented by the following formula (ii): E2 = √ε2 × Tan δ2 (ii) [Here, ε2 indicates the dielectric constant at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours, and Tanδ2 indicates the dielectric tangent at 10 GHz measured by SPDR after absorbing water at 23°C for 24 hours] The E2 value is an index of dielectric properties at 10 GHz after absorbing water at 23°C for 24 hours, calculated based on the above formula, and the ratio of the E2 value to the E1 value calculated based on the above formula (i), (E2 / E1), is within the range of 3.0 to 1.0, preferably within the range of 2.5 to 1.0, and more preferably within the range of 2.2 to 1.0. If E2 / E1 exceeds the above upper limit, when used in a circuit board such as an FPC, the dielectric constant and dielectric loss tangent will increase when wet, and problems such as loss of electrical signals will easily occur on the transmission path of high-frequency signals.

[0028] (moisture absorption rate) In addition, in order to reduce the influence of humidity when the resin film of the present embodiment is used in a circuit board such as an FPC, the moisture absorption rate of the resin film is preferably 0.5% by mass or less, more preferably less than 0.3% by mass. Here, the "moisture absorption rate" means the moisture absorption rate after 24 hours or more have passed under constant temperature and humidity conditions of 23°C and 50% RH (the same meaning applies in this specification). If the moisture absorption rate of the resin film exceeds 0.5% by mass, it becomes susceptible to the influence of humidity when used in a circuit board such as an FPC, and inconveniences such as fluctuations in the transmission speed of high-frequency signals are likely to occur. In other words, if the moisture absorption rate of the resin film exceeds the above range, it becomes easy to absorb water with a high dielectric constant, which leads to an increase in the dielectric constant and dielectric loss tangent, and inconveniences such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur.

[0029] (Storage modulus) The resin film of the present embodiment may have a temperature range of 40 to 250°C in which the storage modulus decreases steeply with increasing temperature. Such a characteristic of the resin film is considered to be a factor in, for example, alleviating internal stress during thermocompression bonding and maintaining dimensional stability after circuit processing. The resin film has a storage modulus of 5×10 at the upper limit temperature of the temperature range. 7 By setting the storage modulus at such a level, even if the temperature is the upper limit of the above-mentioned range, thermocompression bonding at 250° C. or less is possible, and the adhesion can be ensured and dimensional change after circuit processing can be suppressed. In addition, since the resin film of the present embodiment has high thermal expansion but low elasticity, even if the CTE exceeds 30 ppm / K, the internal stress generated during lamination can be alleviated.

[0030] (glass transition temperature) The resin film of the present embodiment preferably has a glass transition temperature (Tg) of 250° C. or less, and more preferably in the range of 40° C. to 200° C. If the resin film has a Tg of 250° C. or less, thermocompression bonding at a low temperature is possible, and the internal stress generated during lamination can be alleviated, and dimensional change after circuit processing can be suppressed. If the resin film has a Tg of more than 250° C., the bonding temperature becomes high, and there is a risk of impairing dimensional stability after circuit processing.

[0031] (Thickness) The thickness of the resin film of the present embodiment is preferably, for example, in the range of 5 μm to 125 μm, and more preferably in the range of 8 μm to 100 μm. If the thickness of the resin film is less than 5 μm, there is a risk of problems such as wrinkles occurring during transportation in the production of the resin film, while if the thickness of the resin film exceeds 125 μm, there is a risk of a decrease in productivity of the resin film.

[0032] <Polyimide> The polyimide of the present embodiment is obtained by imidizing a precursor polyamic acid obtained by reacting a tetracarboxylic anhydride component with a diamine component containing 40 mol % or more of a dimer diamine composition mainly composed of a dimer diamine in which the two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, relative to the total diamine component.

[0033] (Tetracarboxylic acid anhydride component) The tetracarboxylic anhydride used in the polyimide of the present embodiment may include any tetracarboxylic anhydride generally used in thermoplastic polyimides without any particular limitations, but preferably contains tetracarboxylic anhydrides represented by the following general formula (1) in a total amount of 90 mol % or more based on the total tetracarboxylic anhydride components. By containing tetracarboxylic anhydrides represented by the following general formula (1) in a total amount of 90 mol % or more based on the total tetracarboxylic anhydride components, it is preferable that the polyimide is easily compatible in terms of flexibility and heat resistance. If the total amount of tetracarboxylic anhydrides represented by the following general formula (1) is less than 90 mol %, the solvent solubility of the polyimide tends to decrease.

[0034] [ka]

[0035] In general formula (1), X represents a single bond or a divalent group selected from the following formulae:

[0036] [ka]

[0037] In the above formula, Z represents -C6H4-, -(CH2)n-, or -CH2-CH(-OC(=O)-CH3)-CH2-, where n represents an integer of 1 to 20.

[0038] In addition, the term "thermoplastic polyimide" generally refers to a polyimide whose glass transition temperature (Tg) can be clearly confirmed. In the present invention, however, the term "thermoplastic polyimide" refers to a polyimide whose storage modulus at 30°C measured using a dynamic mechanical analyzer (DMA) is 1.0×10 8 Pa or more, and the storage modulus at 300°C is 3.0×10 7 The term "non-thermoplastic polyimide" generally refers to a polyimide that does not soften or exhibit adhesiveness even when heated. In the present invention, however, the term "non-thermoplastic polyimide" refers to a polyimide having a storage modulus of 1.0×10 Pa at 30° C. as measured using a dynamic viscoelasticity measuring device (DMA). 9Pa or more, and the storage modulus at 300°C is 3.0×10 8 This refers to polyimides with a modulus of tensile strength (MPa) or higher.

[0039] Examples of the tetracarboxylic acid anhydride represented by the above general formula (1) include 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride (DSDA), 4,4'-oxydiphthalic acid anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic acid anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester acid anhydride) (TAHQ), and ethylene glycol bisanhydrotrimellitate (TMEG). Among these, when 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is used, the adhesiveness of the polyimide can be improved, and the ketone group present in the molecular skeleton may react with the amino group of the component (B) described below to form a C=N bond, which tends to improve the heat resistance. From this viewpoint, it is preferable that BTDA is contained in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, based on the total tetracarboxylic anhydride components.

[0040] The polyimide of the present embodiment may contain a tetracarboxylic acid residue derived from an acid anhydride other than the tetracarboxylic acid anhydride represented by the above general formula (1) within a range that does not impair the effects of the invention. Such tetracarboxylic acid residues are not particularly limited, and examples thereof include pyromellitic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'- or 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, and bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride.4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2 ,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, ethylene glycol Examples of the tetracarboxylic acid residue include those derived from aromatic tetracarboxylic dianhydrides such as bisanhydrotrimellitate.

[0041] (Diamine component) The polyimide of the present embodiment contains 40 mol % or more, more preferably 60 mol % or more, of the dimer diamine composition based on the total diamine components. By containing the dimer diamine composition in the above amount, the dielectric properties of the polyimide can be improved, and the thermocompression bonding properties can be improved by lowering the glass transition temperature (lowering Tg) of the polyimide, and the internal stress can be alleviated by lowering the elastic modulus.

[0042] (Dimer diamine composition) The dimer diamine composition contains the following component (a) with the amounts of components (b) and (c) being controlled:

[0043] (a) dimer diamine; The dimer diamine of the component (a) means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.

[0044] The dimer diamine composition used may be one in which the dimer diamine content of component (a) is increased to 96% by weight or more, preferably 97% by weight or more, more preferably 98% by weight or more by a purification method such as molecular distillation. By increasing the dimer diamine content of component (a) to 96% by weight or more, the broadening of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that the entire dimer diamine composition (100% by weight) is composed of component (a) dimer diamine.

[0045] (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; The monobasic acid compound having 10 to 40 carbon atoms is a mixture of a monobasic unsaturated fatty acid having 10 to 20 carbon atoms derived from the raw material of dimer acid, and a monobasic acid compound having 21 to 40 carbon atoms which is a by-product during the production of dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monobasic acid compounds with a primary aminomethyl group or an amino group.

[0046] The monoamine compound (b) is a component that suppresses an increase in the molecular weight of the polyimide. During polymerization of the polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal acid anhydride group of the polyamic acid or polyimide to cap the terminal acid anhydride group, thereby suppressing an increase in the molecular weight of the polyamic acid or polyimide.

[0047] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms is a polybasic acid compound mainly composed of a tribasic acid compound having 41 to 80 carbon atoms, which is a by-product during the production of dimer acid. It may also contain a polymerized fatty acid other than dimer acid having 41 to 80 carbon atoms. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.

[0048] The amine compound (c) is a component that promotes an increase in the molecular weight of the polyimide. The trifunctional or higher amino group, the main component of which is a triamine derived from a trimer acid, reacts with the terminal acid anhydride group of the polyamic acid or polyimide, rapidly increasing the molecular weight of the polyimide. In addition, amine compounds derived from polymerized fatty acids other than dimer acids having 41 to 80 carbon atoms also increase the molecular weight of the polyimide, causing gelation of the polyamic acid or polyimide.

[0049] The dimer diamine composition is quantified by gel permeation chromatography (GPC). In order to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, a sample of the dimer diamine composition treated with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard. Using the sample thus prepared, each component is quantified by the area percentage of the GPC chromatogram. The peak start and peak end of each component are the minimum values ​​of each peak curve, and the area percentage of the chromatogram is calculated based on this.

[0050] In the dimer diamine composition used in the present invention, the total area percentage of components (b) and (c) is 4% or less, preferably less than 4%, in terms of the area percentage of a chromatogram obtained by GPC measurement. By keeping the total area percentage of components (b) and (c) at 4% or less, the broadening of the molecular weight distribution of the polyimide can be suppressed.

[0051] The area percentage of the chromatogram of the (b) component is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it in such a range, it is possible to suppress the decrease in the molecular weight of the polyimide, and further to widen the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component. It is not necessary for the (b) component to be contained in the dimer diamine composition.

[0052] The area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it in such a range, a sudden increase in the molecular weight of the polyimide can be suppressed, and further, an increase in the dielectric tangent of the resin film over a wide frequency range can be suppressed. Note that component (c) does not have to be contained in the dimer diamine composition.

[0053] In addition, when the ratio (b / c) of the area percentages of the chromatograms of the components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and less than 1.0. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.

[0054] Furthermore, when the ratio (b / c) of the area percentages of the components (b) and (c) in the chromatograms is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and 1.1 or less. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.

[0055] The weight-average molecular weight of the polyimide is preferably within the range of, for example, 10,000 to 200,000, and within such a range, the weight-average molecular weight of the polyimide is easily controlled. In addition, when applied as an adhesive for FPC, for example, the weight-average molecular weight of the polyimide is more preferably within the range of 20,000 to 150,000, and further preferably within the range of 40,000 to 150,000. When the weight-average molecular weight of the polyimide is less than 20,000, the flow resistance tends to deteriorate. On the other hand, when the weight-average molecular weight of the polyimide exceeds 150,000, the viscosity increases excessively and becomes insoluble in a solvent, and defects such as uneven thickness of the adhesive layer and streaks tend to occur during coating work.

[0056] The dimer diamine composition used in the present invention is preferably purified in order to reduce components other than dimer diamine. Purification method is not particularly limited, but known methods such as distillation and precipitation purification are suitable. The dimer diamine composition before purification can be obtained commercially, for example, PRIAMINE1073 (trade name), PRIAMINE1074 (trade name), PRIAMINE1075 (trade name) and the like manufactured by Croda Japan.

[0057] Examples of diamine compounds other than dimer diamine used in polyimide include aromatic diamine compounds and aliphatic diamine compounds. Specific examples of these compounds include 1,4-diaminobenzene (p-PDA; paraphenylenediamine), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), 4-aminophenyl-4'-aminobenzoate (APAB), 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)biphenyl, bis[1-(3-amino phenoxy)]biphenyl, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'- Methylenedi-o-toluidine, 4,4'-methylenedi-2,6-xylidine, 4,4'-methylene-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 3,3''-diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, bis(p-aminocyclohexyl)methane, bis(p-β-amino- t-butylphenyl)ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-t-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,Examples of diamine compounds include 5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 6-amino-2-(4-aminophenoxy)benzoxazole, and 1,3-bis(3-aminophenoxy)benzene.

[0058] Polyimide can be produced by reacting the above-mentioned tetracarboxylic anhydride component and diamine component in a solvent to generate polyamic acid, which is then subjected to heating and ring-closing. For example, the tetracarboxylic anhydride component and the diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such organic solvents is not particularly limited, but it is preferable to adjust the amount of use so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.

[0059] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is generally advantageously used because it has excellent solvent solubility. The viscosity of the polyamic acid solution is preferably within the range of 500 cps to 100,000 cps. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating operation using a coater or the like.

[0060] The method for imidizing polyamic acid to form polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated in the above-mentioned solvent at a temperature in the range of 80 to 400° C. for 1 to 24 hours is preferably used. The temperature may be constant, or the temperature may be changed during the process.

[0061] In the polyimide of the present embodiment, the dielectric properties, thermal expansion coefficient, tensile modulus, glass transition temperature, etc. can be controlled by selecting the types of the tetracarboxylic anhydride component and diamine component, and the molar ratios of the two or more tetracarboxylic anhydride components or diamine components when they are used. In addition, in the polyimide of the present embodiment, when a plurality of polyimide structural units are present, they may be present as blocks or randomly, but are preferably present randomly.

[0062] The imide group concentration of the polyimide of this embodiment is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to an increase in polar groups, and Tg and elastic modulus increase.

[0063] The polyimide of the present embodiment is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.

[0064] <Adhesive resin composition> The adhesive resin composition of the present embodiment contains, as component (A), the above-mentioned polyimide containing BTDA residues derived from BTDA in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, based on all tetracarboxylic acid residues, and, as component (B), an amino compound having at least two primary amino groups as functional groups. In the present invention, the "BTDA residue" refers to a tetravalent group derived from BTDA.

[0065] (Amino Compounds) In the adhesive resin composition of the present embodiment, examples of the amino compound having at least two primary amino groups as functional groups of the component (B) include dihydrazide compounds, aromatic diamines, and aliphatic amines. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are prone to form crosslinked structures even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form crosslinked structures. In this way, when a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of the dihydrazide compounds include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl dihydrazide, and the like. Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoedioic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.

[0066] In addition, the above amino compounds, such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines, can also be used in combination of two or more kinds beyond categories, such as a combination of (I) and (II), a combination of (I) and (III), or a combination of (I), (II) and (III).

[0067] In addition, from the viewpoint of making the network structure formed by the crosslinking with the amino compound of component (B) denser, the molecular weight of the amino compound of component (B) used in the present invention (weight average molecular weight when the amino compound is an oligomer) is preferably 5,000 or less, more preferably 90 to 2,000, and even more preferably 100 to 1,500. Among these, an amino compound having a molecular weight of 100 to 1,000 is particularly preferred. If the molecular weight of the amino compound is less than 90, only one amino group of the amino compound forms a C=N bond with a ketone group of the polyimide resin, and the surroundings of the remaining amino groups become three-dimensionally bulky, so that the remaining amino groups tend not to form a C=N bond.

[0068] When the ketone group of the BTDA residue is crosslinked with the amino compound, the amino compound is added to a resin solution containing the component (A) to cause a condensation reaction between the ketone group in the polyimide and the primary amino group of the amino compound. This condensation reaction hardens the resin solution to become a cured product. In this case, the amount of the amino compound added is such that the total amount of the primary amino group is 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol per mol of the ketone group. If the amount of the amino compound added is less than 0.004 mol of the primary amino group per mol of the ketone group, crosslinking by the amino compound is insufficient, and the heat resistance after curing tends to be difficult to be expressed, and if the amount of the amino compound added exceeds 1.5 mol, the unreacted amino compound acts as a thermoplasticizer, which tends to reduce the heat resistance of the adhesive layer.

[0069] The conditions of the condensation reaction for forming crosslinks are not particularly limited as long as the ketone group in the polyimide (A) reacts with the primary amino group in the amino compound (B) to form an imine bond (C=N bond). The temperature of the thermal condensation is preferably within the range of, for example, 120 to 220°C, more preferably within the range of 140 to 200°C, for the purpose of releasing water produced by condensation out of the system, or for the purpose of simplifying the condensation step when the thermal condensation reaction is carried out subsequently to the synthesis of the polyimide (A). The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm. -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.

[0070] The thermal condensation of the ketone group of the polyimide (A) and the primary amino group of the amino compound (B) can be carried out, for example, as follows: (1) A method in which, following the synthesis (imidization) of the polyimide (A), the amino compound (B) is added and heated; (2) A method in which an excess amount of an amino compound is charged in advance as a diamine component, and following synthesis (imidization) of the polyimide of component (A), the remaining amino compound that is not involved in imidization or amidation is heated together with the polyimide as component (B), or (3) This can be achieved by a method in which the polyimide composition, component (A), to which the amino compound, component (B), has been added is processed into a predetermined shape (for example, after being applied to a substrate or formed into a film), and then heated.

[0071] Although the formation of imine bonds has been described as the formation of a crosslinked structure to impart heat resistance to the polyimide of component (A), the present invention is not limited thereto, and the method for curing the polyimide of component (A) can also involve blending and curing, for example, epoxy resins, epoxy resin curing agents, active ester compounds, benzoxazine resins, cyanate ester resins, maleimides, activated ester resins, resins having a phenyl ether skeleton or a styrene skeleton having an unsaturated bond, etc. Here, the active ester compound functions as a curing agent for epoxy resins and has an active ester.

[0072] In addition, the adhesive resin composition of the present embodiment preferably contains an inorganic filler (C) as an optional component in addition to the polyimide (A) and amino compound (B). If necessary, other optional components such as plasticizers, epoxy resins, fluororesins, and olefin resins, curing accelerators, coupling agents, fillers, pigments, solvents, and flame retardants can be appropriately blended. However, some plasticizers contain a large number of polar groups, which may promote the diffusion of copper from the copper wiring, so it is preferable to avoid using plasticizers as much as possible.

[0073] The adhesive resin composition of the present embodiment has excellent flexibility and thermoplasticity when used to form an adhesive layer, and has favorable properties as an adhesive for coverlay films that protect wiring parts of FPCs, rigid-flex circuit boards, and the like.

[0074] <Coverlay film> The coverlay film of the present embodiment is composed of an adhesive layer made of the above-mentioned resin film or the above-mentioned adhesive resin composition, and a coverlay film material layer. The coverlay film material is not particularly limited, but for example, polyimide resin films such as polyimide resins, polyetherimide resins, and polyamideimide resins, polyamide resin films, and polyester resin films can be used. Among these, it is preferable to use a polyimide resin film having excellent heat resistance. The thickness of the coverlay film material layer is not particularly limited, but is preferably, for example, 5 μm or more and 100 μm or less. The thickness of the adhesive layer is not particularly limited, but is preferably, for example, 10 μm or more and 50 μm or less.

[0075] In addition, the coverlay film material may contain a black pigment in order to effectively exhibit light-blocking properties, concealing properties, design properties, etc., and may also contain optional components such as matte pigments that suppress the gloss of the surface, as long as the effect of improving the dielectric properties is not impaired.

[0076] The coverlay film of the present embodiment can be produced, for example, by the method exemplified below. As a first method, an adhesive resin composition that will become the adhesive layer is applied in a solution state (e.g., a varnish-like state containing a solvent) to one side of a film material for a coverlay, and then the resulting mixture is thermocompressed at a temperature of, for example, 60 to 220°C to form a coverlay film having a film material layer for a coverlay and an adhesive layer.

[0077] As a second method, the adhesive resin composition for the adhesive layer is applied in a solution state (for example, in a varnish state containing a solvent) onto any substrate, dried at a temperature of, for example, 80 to 180° C., and then peeled off to form a resin film for the adhesive layer, and this resin film is thermocompressed to a film material for the coverlay at a temperature of, for example, 60 to 220° C., thereby forming the coverlay film of the present embodiment. The adhesive layer can also be used by applying the adhesive resin composition in a solution state onto any substrate, for example, by screen printing to form a coating film, and drying this at a temperature of, for example, 80 to 180° C. to form a film.

[0078] <Circuit board> The circuit board of the present embodiment includes a base material, a wiring layer formed on the base material, and a coverlay film that covers the wiring layer. Although there is no particular limitation on the base material of the circuit board, in the case of an FPC, it is preferable to use a material similar to the above-mentioned coverlay film material, and it is preferable to use a base material made of a polyimide resin.

[0079] <Resin-coated copper foil> The resin-coated copper foil of the present embodiment comprises an adhesive layer made of the above-mentioned resin film or the above-mentioned adhesive resin composition, and a copper foil.

[0080] The thickness of the adhesive layer is preferably, for example, within the range of 0.1 to 125 μm, and more preferably within the range of 0.3 to 100 μm. If the thickness of the adhesive layer is less than the lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer exceeds the upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of lowering the dielectric constant and the dielectric loss tangent, the thickness of the adhesive layer is preferably 3 μm or more.

[0081] In the resin-coated copper foil of the present embodiment, the material of the copper foil is preferably one mainly composed of copper or a copper alloy. The thickness of the copper foil is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the copper foil is preferably 5 μm. The copper foil may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil may be used as the copper foil.

[0082] The resin-coated copper foil of the present embodiment may be prepared, for example, by preparing a resin film, sputtering a metal to form a seed layer, and then forming a copper layer by, for example, copper plating, or by laminating the resin film with copper foil by a method such as thermocompression bonding.

[0083] Furthermore, the resin-coated copper foil of the present embodiment may be prepared by casting a coating liquid for forming a resin layer on a copper foil, drying it to form a coating film, and then heat treating it.

[0084] <Metal-clad laminate> The metal-clad laminate of the present embodiment includes an insulating resin layer, an adhesive layer made of the resin film or the adhesive resin composition laminated on at least one surface of the insulating resin layer, and the adhesive Agent and a metal layer laminated on the insulating resin layer via a layer, and is a so-called three-layer metal-clad laminate. adhesive layer However, it is sufficient that the insulating resin layer is provided on one or both sides thereof, and the metal layer is provided on one or both sides thereof via an adhesive layer. In other words, the metal-clad laminate of the present embodiment may be a single-sided metal-clad laminate or a double-sided metal-clad laminate. A single-sided or double-sided FPC can be manufactured by processing the metal layer of the metal-clad laminate of the present embodiment into a wiring circuit by etching or the like.

[0085] The insulating resin layer is not particularly limited as long as it is made of a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenol resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., but it is preferable that it is made of polyimide. The polyimide layer constituting the insulating resin layer may be a single layer or multiple layers, but it is preferable that it includes a non-thermoplastic polyimide layer.

[0086] The thickness of the insulating resin layer is preferably, for example, in the range of 1 to 125 μm, and more preferably in the range of 5 to 100 μm. If the thickness of the insulating resin layer is less than the above lower limit, problems such as insufficient electrical insulation may occur. On the other hand, if the thickness of the insulating resin layer exceeds the above upper limit, problems such as the metal-clad laminate being more likely to warp may occur. In addition, the thickness of the insulating resin layer and the adhesion Agent Ratio of thickness to layer (thickness of insulating resin layer / adhesive Agent The thickness of the layer is preferably within a range of 0.5 to 2.0. By setting the ratio in this range, warping of the metal-clad laminate can be suppressed.

[0087] The insulating resin layer may contain a filler as necessary. Examples of the filler include silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, and metal salts of organic phosphinic acid. These may be used alone or in combination of two or more.

[0088] The thickness of the adhesive layer is preferably, for example, within the range of 0.1 to 125 μm, and more preferably within the range of 0.3 to 100 μm. In the three-layer metal-clad laminate of the present embodiment, if the thickness of the adhesive layer is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of reducing the dielectric constant and dielectric loss tangent of the entire insulating layer, which is a laminate of an insulating resin layer and an adhesive layer, the thickness of the adhesive layer is preferably 3 μm or more.

[0089] The material of the metal layer in the metal-clad laminate of the present embodiment is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferred.

[0090] The thickness of the metal layer is not particularly limited, but for example, when a copper foil is used as the metal layer, it is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the copper foil is preferably 5 μm. When a copper foil is used, it may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil may be used as the copper foil.

[0091] When a copper foil is used as the metal layer, the copper foil preferably comprises a base copper foil and an anti-rust treatment layer formed on the surface of the base copper foil on the side on which the adhesive layer (or insulating resin layer) is formed. In addition to the above-mentioned anti-rust treatment, the surface of the copper foil may be subjected to a surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, silane coupling agent, etc., for the purpose of improving adhesive strength.

[0092] <Multilayer circuit board> The multilayer circuit board of the present embodiment comprises a laminate including a plurality of stacked insulating resin layers, and one or more conductor circuit layers embedded inside the laminate, at least one of the plurality of insulating resin layers being formed of an adhesive layer having adhesive properties and covering the conductor circuit layer, the adhesive layer being made of the above-mentioned resin film or the above-mentioned adhesive resin composition.

[0093] The multilayer circuit board of the present embodiment has at least two insulating resin layers and at least two conductor circuit layers, at least one of which is a conductor circuit layer covered with an adhesive layer. The adhesive layer covering the conductor circuit layer may partially cover the surface of the conductor circuit layer, or may cover the entire surface of the conductor circuit layer. The multilayer circuit board of the present embodiment may also have a conductor circuit layer exposed on the surface of the multilayer circuit board. It may also have an interlayer connection electrode (via electrode) in contact with the conductor circuit layer.

[0094] The conductor circuit layer is formed by forming a conductor circuit in a predetermined pattern on one or both sides of an insulating resin layer. The conductor circuit may be formed by patterning the surface of the insulating resin layer or by damascene (embedded) patterning. EXAMPLES

[0095] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.

[0096] [Method for measuring amine value] Approximately 2 g of the dimer diamine composition is weighed into a 200-250 mL Erlenmeyer flask, and phenolphthalein is used as an indicator. A 0.1 mol / L ethanolic potassium hydroxide solution is dropped into the solution until the solution turns light pink, and the solution is dissolved in approximately 100 mL of neutralized butanol. 3-7 drops of phenolphthalein solution are added thereto, and titration is performed with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Five drops of bromophenol blue solution are added thereto, and titration is performed with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow. The amine value is calculated according to the following formula (1). Amine value = {(V2 x C2) - (V1 x C1)} x M KOH / m (1) Here, the amine value is expressed as mg-KOH / g, and M KOH is the molecular weight of potassium hydroxide, 56.1. V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent 0.1 mol / L ethanolic potassium hydroxide solution and 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.

[0097] [Measurement of weight average molecular weight (Mw) of polyimide] The weight average molecular weight was measured by gel permeation chromatography (HLC-8220GPC, manufactured by Tosoh Corporation). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.

[0098] [Calculation of GPC and chromatogram area percentage] For GPC, 20 mg of the dimer diamine composition was pretreated with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of THF to prepare a 100 mg solution, which was then diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a Tosoh Corporation product name: HLC-8220GPC under the following conditions: column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40° C., injection volume: 50 μL. Cyclohexanone was used as a standard substance to correct the elution time.

[0099] In this case, the retention times were adjusted so that the peak top of the cyclohexanone main peak was at a retention time of 27 to 31 minutes, and the period from the peak start to the peak end of the cyclohexanone main peak was 2 minutes, and the peak top of the main peak excluding the cyclohexanone peak was at a retention time of 18 to 19 minutes, and the period from the peak start to the peak end of the main peak excluding the cyclohexanone peak was at a retention time of 2 minutes to 4 minutes 30 seconds, (a) Component represented by the main peak; (b) A component represented by a GPC peak detected at a time later than the minimum retention time of the main peak; (c) Components represented by GPC peaks detected at earlier retention times than the minimum value of the main peak on the earlier side; was detected.

[0100] [Dielectric property evaluation] Using a vector network analyzer (manufactured by Agilent, product name: Vector Network Analyzer E8363C) and an SPDR resonator, the resin sheet (resin sheet after curing) was left for 24 hours under conditions of temperature: 23°C and humidity: 50%, and then the dielectric constant (ε1) and dielectric loss tangent (Tan δ1) at a frequency of 10 GHz were measured. E1, which is an index showing the dielectric properties of the resin laminate, was calculated based on the above formula (i). In addition, after absorbing water for 24 hours at 23°C, the dielectric constant (ε2) and dielectric loss tangent (Tan δ2) at a frequency of 10 GHz of the resin sheet (resin sheet after curing) were measured. E2, which is an index showing the dielectric properties of the resin laminate, was calculated based on the above formula (ii).

[0101] [Moisture absorption rate measurement] Two test pieces (4 cm wide × 25 cm long) of the resin sheet (resin sheet after curing) were prepared and dried at 80° C. for 1 hour. Immediately after drying, they were placed in a constant temperature and humidity chamber at 23° C. / 50% RH and left to stand for 24 hours or more. The weight change before and after was calculated using the following formula. Moisture absorption rate (weight %) = [(weight after moisture absorption - weight after drying) / weight after drying] × 100

[0102] [Glass transition temperature (Tg) and storage modulus] The glass transition temperature (Tg) and storage modulus were measured using a 5mm x 20mm resin sheet (cured resin sheet) at a heating rate of 4°C / min from 30°C to 400°C and a frequency of 11Hz using a dynamic viscoelasticity measuring device (DMA: manufactured by UBM, product name: E4000F). The temperature at which the change in modulus of elasticity (tan δ) was maximum was taken as the glass transition temperature.

[0103] [Tensile modulus] The tensile modulus was measured by the following procedure. First, a test piece (width 12.7 mm × length 127 mm) was prepared from the resin sheet (resin sheet after curing) using a tension tester (Tensilon manufactured by Orientec). A tensile test was performed at 50 mm / min using this test piece to determine the tensile modulus at 25°C.

[0104] [Warpage evaluation method] The warpage was evaluated as follows: A polyimide adhesive was applied to a 25μm thick Kapton film or 12μm thick copper foil so that the thickness after drying was 25μm. In this state, the Kapton film and copper foil were placed on the bottom, and the average height of the warpage at the four corners of the film was measured, with 5mm or less being rated as "good" and over 5mm being rated as "no good."

[0105] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride (manufactured by Evonik, trade name: BTDA Ultra Pure) BisDA: 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride (manufactured by SABIC Innovative Plastics Japan, LLC, product name: BisDA-1000) BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride ODPA: 4,4'-oxydiphthalic anhydride DDA1: Product name: PRIAMINE 1075 manufactured by Croda Japan Co., Ltd., distilled and purified (component a: 98.2% by weight, component b: 0%, component c: 1.9%, amine value: 206 mg KOH / g) DDA2: Product name: PRIAMINE 1075 manufactured by Croda Japan Co., Ltd., distilled and purified (component a: 99.2% by weight, component b: 0%, component c: 0.8%, amine value: 210 mg KOH / g) N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone APB: 1,3-bis(3-aminophenoxy)benzene BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane In the above DDA1 and DDA2, the "%" of the b component and the c component means the area percentage of the chromatogram in the GPC measurement. The molecular weights of DDA1 and DDA2 were calculated by the following formula (1). Molecular weight = 56.1 × 2 × 1000 / amine value (1)

[0106] [Example 1] A polyamic acid solution was prepared by charging 55.51 g of BTDA (0.1721 mol), 94.49 g of DDA1 (0.1735 mol), 210 g of NMP, and 140 g of xylene into a 1000 ml separable flask and thoroughly mixing at 40° C. for 1 hour. The polyamic acid solution was heated to 190° C., heated and stirred for 10 hours, and 125 g of xylene was added to complete the imidization, preparing polyimide solution 1 (solid content: 30% by weight, weight average molecular weight: 82,900).

[0107] [Examples 2 to 12] Polyimide solutions 2 to 12 were prepared in the same manner as in Example 1, except that the raw material compositions shown in Table 1 were used.

[0108] [Table 1]

[0109] As shown in Table 1, in Examples 1 to 12, polyimides having weight average molecular weights in the range of 40,000 to 150,000 were obtained.

[0110] [Example 13] 2.7 g of N-12 (0.0105 mol; equivalent to 0.35 mol of primary amino group per 1 mol of BTDA ketone group) was mixed with 169.49 g (50 g as solid content) of the polyimide solution 1 obtained in Example 1, diluted with 6.0 g of NMP, and further stirred for 1 hour to obtain adhesive resin composition 1.

[0111] The obtained adhesive resin composition 1 was applied to one side of a release PET film (Higashiyama Film Co., Ltd., product name: HY-S05, length x width x thickness = 200 mm x 300 mm x 25 μm), dried at 80°C for 15 minutes, and the adhesive layer was peeled off from the release PET film to prepare a resin film 1 with a thickness of 25 μm. This resin film 1 was heated in an oven at a temperature of 160°C for 2 hours to obtain an evaluation sample 1. The results of the evaluation of various characteristics are shown in Table 2.

[0112] [Examples 14 to 24] Adhesive resin compositions 2 to 12 and resin films 2 to 12 were prepared in the same manner as in Example 13, except that polyimide solutions 2 to 12 were used instead of polyimide solution 1, and then evaluation samples 2 to 12 were obtained. The results of the evaluation of various characteristics are shown in Table 2.

[0113] [Table 2]

[0114] [Example 25] The adhesive resin composition 1 obtained in Example 13 was applied to one side of a polyimide film (manufactured by DuPont, product name: Kapton 100EN-S, ε1 = 3.5, tan δ1 = 0.012, length × width × thickness = 200 mm × 300 mm × 25 μm) and dried at 80°C for 15 minutes to obtain a coverlay film 1 with an adhesive layer thickness of 25 μm. The warpage state of the obtained coverlay film was "good".

[0115] [Examples 26 to 36] Coverlay films 2 to 12 were produced in the same manner as in Example 25, except that adhesive resin compositions 2 to 12 were used instead of adhesive resin composition 1. The warpage state of the obtained coverlay films 2 to 12 was all "good".

[0116] [Example 37] The adhesive resin composition 1 obtained in Example 13 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 15 minutes to obtain a resin-coated copper foil 1 having an adhesive layer thickness of 25 μm. The warpage state of the obtained resin-coated copper foil 1 was “good”.

[0117] [Example 38] The adhesive resin composition 4 obtained in Example 16 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 30 minutes to obtain a resin-coated copper foil 2 having an adhesive layer thickness of 50 μm.

[0118] [Example 39] An adhesive resin composition 4 was applied onto the resin surface of the resin-coated copper foil 2 obtained in Example 38, and dried at 80° C. for 30 minutes to obtain a resin-coated copper foil 3 having an adhesive layer thickness of 100 μm in total.

[0119] [Example 40] The adhesive resin composition 1 obtained in Example 13 was applied to one side of a release PET film (Higashiyama Film Co., Ltd., product name: HY-S05, length x width x thickness = 200 mm x 300 mm x 25 μm), dried at 80 ° C for 30 minutes, and the adhesive layer was peeled off from the release PET film to obtain a resin film 1' having a thickness of 50 μm. On an electrolytic copper foil having a thickness of 12 μm, a resin film 1', a polyimide film (manufactured by DuPont, product name: Kapton 100-EN, thickness 25 μm, ε1 = 3.6, tan δ1 = 0.084), a resin film 1', and an electrolytic copper foil having a thickness of 12 μm were sequentially laminated, and the laminate was pressure-bonded at a temperature of 160 ° C, a pressure of 0.8 MPa, for 2 minutes using a vacuum laminator, and then heat-treated at 160 ° C for 4 hours to obtain a copper-clad laminate 1.

[0120] [Example 41] The adhesive resin composition 1 obtained in Example 13 was applied to one side of a polyimide film (manufactured by DuPont, product name: Kapton 50EN, ε1 = 3.6, tan δ1 = 0.086, length x width x thickness = 200 mm x 300 mm x 12 μm), and dried at 80 ° C for 15 minutes to obtain a coverlay film 1' with an adhesive layer thickness of 25 μm. The coverlay film 1' was laminated on an electrolytic copper foil with a thickness of 12 μm so that the adhesive resin composition 1 side of the coverlay film 1' was in contact with the copper foil, and the film was pressed using a vacuum laminator at a temperature of 160 ° C, a pressure of 0.8 MPa, for 2 minutes, and then heat-treated at 160 ° C for 2 hours to obtain a copper-clad laminate 2.

[0121] [Example 42] The resin film 1 (thickness: 25 μm) obtained in Example 13 and the coverlay film 1' obtained in Example 41 were laminated on a rolled copper foil of 12 μm in thickness so that the polyimide film side of the coverlay film 1' obtained in Example 41 was in contact with the resin film 1, and then the resin film 1 (thickness: 25 μm) and the rolled copper foil of 12 μm in thickness were laminated in sequence, and the resultant was pressed using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa for 2 minutes, and then heat-treated at 160°C for 2 hours to obtain a copper-clad laminate 3.

[0122] [Example 43] Two sheets of the resin-coated copper foil 3 obtained in Example 39 were prepared, and a polyimide film (manufactured by DuPont, product name: Kapton 200-EN, thickness 50 μm, ε1 = 3.6, tan δ1 = 0.084) was laminated to the adhesive resin composition 4 side of one of the resin-coated copper foils 3, and the other resin-coated copper foil 3 was laminated so that the adhesive resin composition 4 side was in contact with the polyimide film, and the two were pressed together using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa for 5 minutes, and then heat-treated at 160°C for 4 hours to obtain a copper-clad laminate 4.

[0123] [Example 44] The adhesive resin composition 1 obtained in Example 13 was applied to the polyimide side of a single-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ, length x width x thickness = 200 mm x 300 mm x 25 μm), and dried at 80 ° C. for 30 minutes to obtain an adhesive-coated copper-clad laminate 1 having an adhesive layer thickness of 50 μm. The single-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ) was laminated so that the polyimide of the single-sided copper-clad laminate was in contact with the adhesive resin composition 1 side of the adhesive-coated copper-clad laminate 1, and the laminate was pressed at a temperature of 160 ° C. and a pressure of 4.0 MPa for 120 minutes using a small precision press to obtain a copper-clad laminate 5.

[0124] [Example 45] The adhesive-coated copper-clad laminates 1 obtained in Example 44 were laminated together with the adhesive resin composition 1 sides in contact, and then pressed together using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain copper-clad laminate 6.

[0125] [Example 46] The resin film 4 (thickness 25 μm) obtained in Example 16 was laminated to the polyimide side of a single-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ), and then the single-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ) was laminated so that the polyimide side of the single-sided copper-clad laminate was in contact with the resin film 4, and the laminate was pressed using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain a copper-clad laminate 7.

[0126] [Example 47] The adhesive resin composition 1 obtained in Example 13 was applied to one side of a release PET film (Higashiyama Film Co., Ltd., product name: HY-S05, length x width x thickness = 200 mm x 300 mm x 25 μm), dried at 80 ° C for 15 minutes, and the adhesive layer was peeled off from the release PET film to obtain a resin film 1 ″ having a thickness of 15 μm. The resin film 1 ″ was laminated on the polyimide side of a single-sided copper-clad laminate (Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ), and further laminated so that the polyimide side of the single-sided copper-clad laminate (Nippon Steel Chemical & Material Co., Ltd., product name: ESPANEX FC12-25-00UEJ) was in contact with the resin film 1 ″, and pressed using a small precision press at a temperature of 160 ° C, a pressure of 4.0 MPa, for 120 minutes to obtain a copper-clad laminate 8.

[0127] [Example 48] A double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex FB12-25-00UEY) was prepared, and the copper foil on one side of the laminate was subjected to circuit processing by etching to form a conductor circuit layer, thereby preparing a wiring board 1. In addition, the copper foil on one side of the double-sided copper-clad laminate (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex FB12-25-00UEY) was removed by etching to prepare a copper-clad laminate 9. The resin film 1 obtained in Example 13 was sandwiched between the surface of the conductor circuit layer side of the wiring board 1 and the surface of the insulating base layer side of the copper-clad laminate 9, and in the laminated state, the two were thermocompressed at a temperature and pressure of 4.0 MPa for 120 minutes to prepare a multilayer circuit board 1.

[0128] [Example 49] A copper-clad laminate 10 was prepared using an insulating substrate made of a liquid crystal polymer film (manufactured by Kuraray Co., Ltd., product name: CT-Z, thickness: 50 μm, CTE: 18 ppm / K, heat distortion temperature: 300 ° C., dielectric constant: 3.40, dielectric tangent: 0.0022) and copper foil (electrolytic copper foil, thickness: 9 μm, surface roughness Rz: 2.0 μm) on both sides thereof, and a circuit board 2 was prepared in which the copper foil on one side was subjected to circuit processing by etching to form a conductor circuit layer. In addition, the copper foil on one side of the copper-clad laminate 10 was removed by etching to prepare a copper-clad laminate 10'. The resin film 1 obtained in Example 13 was sandwiched between the surface of the conductor circuit layer side of the wiring board 2 and the surface of the insulating substrate layer side of the copper-clad laminate 10', and in the laminated state, the resin film 1 was thermocompressed at a temperature and pressure of 4.0 MPa for 120 minutes to prepare a multilayer circuit board 2.

[0129] [Example 50] The coverlay film 1' obtained in Example 41 was laminated so that a release PET film (manufactured by Higashiyama Film Co., Ltd., product name: HY-S05) was in contact with the adhesive composition 1 side, and pressure-bonded for 2 minutes at a temperature of 160 ° C. and a pressure of 0.8 MPa using a vacuum laminator. Thereafter, the adhesive resin composition 1 obtained in Example 13 was applied to the polyimide film side of the coverlay film 1' so that the thickness after drying was 25 μm, and dried at 80 ° C. for 15 minutes. Furthermore, the release PET film (manufactured by Higashiyama Film Co., Ltd., product name: HY-S05) was laminated so that it was in contact with the dried adhesive composition 1 side, and pressure-bonded for 2 minutes at a temperature of 160 ° C. and a pressure of 0.8 MPa using a vacuum laminator to prepare a polyimide adhesive laminate 1 having adhesive layers on both sides of the polyimide film.

[0130] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible.

Claims

1. A resin film containing polyimide as a resin component, the polyimide is obtained by reacting a tetracarboxylic anhydride component with a diamine component, and the diamine component contains 40 mol % or more of a dimer diamine composition containing 98.2 wt % or more of a dimer diamine composition as a main component, the dimer diamine being obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups, relative to the total diamine component; The dimer diamine composition is measured by gel permeation chromatography, and the area percentage of the chromatogram is determined to be the following components (a) to (c): (a) dimer diamine; (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The content of the component (b) is 0% and the content of the component (c) is 2% or less, the ratio (b / c) of the area percentages of the chromatograms of the component (b) and the component (c) is less than 1; a molar ratio of the tetracarboxylic anhydride component to the diamine component (tetracarboxylic anhydride component / diamine component) is 0.97 or more and 1.008 or less, Configurations I and II below: I) Formula (i) below: E 1 =√ε 1 ×Tắẹδ 1 ・・・(i) [where ε 1 indicates the dielectric constant at 10 GHz measured by a split post dielectric resonator (SPDR) after 24 hours of humidity conditioning under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH, and Tan δ 1 indicates the dielectric tangent at 10 GHz measured by SPDR after 24 hours of humidity conditioning under constant temperature and humidity conditions of 23° C. and 50% RH. E is an index showing the dielectric properties at 10 GHz after 24 hours of humidity conditioning under constant temperature and humidity conditions of 23 ° C. and 50% RH, calculated based on 1 a value of 0.010 or less; II) Formula (ii) below: E 2 =√ε 2 ×Tanδ 2 ・・・(ii) [where ε 2 indicates the dielectric constant at 10 GHz measured by SPDR after absorbing water at 23° C. for 24 hours, and Tan δ 2 indicates the dielectric tangent at 10 GHz measured by SPDR after absorbing water at 23° C. for 24 hours. E is an index showing the dielectric properties at 10 GHz after absorbing water at 23 ° C. for 24 hours, calculated based on 2 In value, The above E 1 E for value 2 The ratio of values ​​(E 2 / E 1 ) is within the range of 3.0 to 1.0; A resin film characterized by satisfying the above.

2. A coverlay film having an adhesive layer and a coverlay film material layer laminated thereon, A coverlay film, wherein the adhesive layer is made of the resin film according to claim 1.

3. A circuit board comprising a substrate, a wiring layer formed on the substrate, and the coverlay film according to claim 2 that covers the wiring layer.

4. A resin-coated copper foil having an adhesive layer and a copper foil laminated thereon, 2. A resin-coated copper foil, wherein the adhesive layer is made of the resin film according to claim 1.

5. A metal-clad laminate having an insulating resin layer, an adhesive layer laminated on at least one surface of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, A metal-clad laminate, wherein the adhesive layer is made of the resin film according to claim 1.

6. A multilayer circuit board comprising a laminate including a plurality of laminated insulating resin layers, and one or more conductor circuit layers embedded in the laminate, At least one of the plurality of insulating resin layers is formed of an adhesive layer having adhesiveness and covering the conductor circuit layer, 2. A multilayer circuit board, comprising the adhesive layer comprising the resin film according to claim 1.

7. A polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component, the diamine component containing 40 mol % or more of a dimer diamine composition containing 98.2 wt % or more of a dimer diamine composition as a main component, the dimer diamine being obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups, relative to the total diamine component; The dimer diamine composition is measured by gel permeation chromatography, and the area percentage of the chromatogram is determined to be the following components (a) to (c): (a) dimer diamine; (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The content of the component (b) is 0% and the content of the component (c) is 2% or less, the ratio (b / c) of the area percentages of the chromatograms of the component (b) and the component (c) is less than 1; A polyimide characterized in that the molar ratio of the tetracarboxylic anhydride component to the diamine component (tetracarboxylic anhydride component / diamine component) is 0.97 or more and 1.008 or less.

8. 8. The polyimide according to claim 7, wherein the polyimide contains 50 mol % or more of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) based on the total amount of the tetracarboxylic anhydride component.

9. The following components (A) and (B): (A) the polyimide according to claim 8, and (B) an amino compound having at least two primary amino groups as functional groups; Including, An adhesive resin composition comprising the component (B) such that the total amount of the primary amino groups is within the range of 0.004 mol to 1.5 mol per 1 mol of ketone groups of the BTDA residue derived from BTDA in the component (A).

Citation Information

Patent Citations

  • Crosslinked polyimide resin, adhesive resin composition and cured product thereof, cover lay film and circuit board

    JP2013001730A

  • Copper foil with resin, copper-clad laminate, printed wiring board and multilayer wiring board

    JP2017119361A

  • Binding agent and article bound by binding agent

    JP2017137375A

  • Metal-clad laminate, adhesive sheet, adhesive polyimide resin composition, and circuit board

    JP2018140544A